Managing behavioral issues in child care and schools : a quick reference guide - Gleason, Mary Margaret, 1951-; Trigg, Allison Boothe (American Academy of Pediatrics, 2020)
This quick-reference guide is designed for those who work with young children in child care and school settings. Topics cover social-emotional development, biting, napping difficulties, PTSD, gender development, self-stimulation behaviors, and more. In addition to behavioral issues commonly seen in small children, the editors touch on epigenetics, medications, toxic stress, ACEs (adverse childhood experiences), and how to help children who have undergone traumatic experiences